Désirer le monde : le rôle de l’atmosphère au cinéma dans la subjectivation éthique et esthétique du spectateur - Louise Bouvet-Zieleskiewicz (Ambiances)
The atmosphere in cinema is the site of theoretical exploration of the links between world and subject, from a perspective that traditionally sees atmosphere as modular, as an agreement between our mood and the “climate of the world”. This article will seek to clarify the ethical and poetic links between the atmosphere and the subject. Far from being only an encompassing ambiance in which the subject would be immersed, atmosphere is seen here as an active instance which shapes the spectator subject, participates in the creation of the spectator’s personality and prompts a form of continual renewal of his curiosity and manner of perception. L’art et le monde by Charles Bobant will allow us to update this productive dimension of atmosphere. The latter participates in the process of subjectification of the spectator, the desire to pierce the atmosphere giving birth to a real subject of cinema, of which Stanley Cavell would be the paradigmatic example. This productive dimension ends in a form of circularity: faced with the danger of the annihilation of the atmosphere by the spectatorial desire, an ethics of the spectator based on delicacy must be theorised.